Employee Job Satisfaction in Furniture Manufacturing Companies in the Slovak Republic - Silvia Lorincová (University of Zagreb, Faculty of Forestry and Wood Technology, 2017)
The research was focused on the comprehensive understanding of motivation factors that affected empoyee job satisfaction in furniture manufacturing companies in the Slovak Republic in 2015. Questionnaire analysis was selected as the key research method. Questionnaires consisted of 36 most motivating factors organized into 5 sub-cathegories, analyzed on the basis of the degree of satisfaction for respondents. Based on the collected data, top 10 motivation factors, which the employees of Slovak furniture manufacturing companies rated as the most satisfying, were identified. According to respondents, 3 most satisfying factors included physical work demands, “interestingness” of work and the ability to use the qualification. Research outcomes resulted in a series of recommendations for the furniture manufacturing companies to focus on in order to boost employee job satisfaction with regards to the fact that only well-motivated employees can increase the efficiency of the whole enterprise.